THE ANALYSIS OF OUTDOOR FACILITIES OF THE BAY VILLAS RESORT TANJUNG LESUNG, BANTEN. - Ramadhan Gema Pratama; Silia Yuslim; Etty Indrawati; Olivia Seanders (Universitas Trisakti, 2023)
Tourist interest continues to increase, especially in tourism development in hospitality and resort services which is increasingly being considered. The development of resort hotels has also begun to develop in big cities, one of which is Tanjung Lesung, Banten. The Tanjung Lesung Banten area is a beach resort tourist area close to Jakarta. Resort hotels are buildings that need attention, and outdoor space aspects must also be considered to attract visitors to Hotel Resort The Bay Villas Resort, Tanjung Lesung, Banten. This research was done to formulate the design of outdoor facilities at The Bay Villas Resort and the addition of the Modern Beach Resort concept. Writing the design of outdoor facilities for The Bay Villas Resort was developed based on the results of literature studies and observations that can be used as consideration for proposals in developing the design of outdoor facilities for The Bay Villas Resort. The research method used is a descriptive static analysis method of questionnaires and questionnaire variables studied using the Likert scale 1: 3 analysis method. Both primary and secondary data are collected and then analyzed to have functions related to the design of outdoor facilities at The Bay Villas Resort, Tanjung Lesung Banten gets the right design concept and quality.